EFFECT OF CRYOGENIC COOLING ENVIRONMENT USING CO2 ON CUTTING TEMPERATURE IN TURNING PROCESS - BolewarA.B.; Shinde V.B. (International Journal of Innovations in Engineering Research and Technology, 2021)
In this study, the turning process is carried out by machining AISI 1045 steel with the CNMG 120412 multi-coated carbide insert. The machining operations were carried out in different machining environments. The effect of cryogeniccooling with CO2 as the cutting coolants is studied and compared, with dry and conventional wet machining in terms of the cutting temperature. It was observed that cryogenic machining is an effective alternative method, to reduce the cutting temperature arises during the machining process.Reduction of cutting temperature in the range of 9 –19% was observed at high speed (145 m/min) compared to wet machining. The outcome of the study can be useful for the industry and practitioners to improve productivityand reduceenvironmental impact due to use of coolant